Global, regional, and country-level cost of leptospirosis due to loss of productivity in humans. - Suneth Agampodi; Sajaan Gunarathna; Jung-Seok Lee; Jean-Louis Excler (Public Library of Science (PLoS), 2023)
Background Leptospirosis, a prevalent zoonotic disease with One Health priority and a disease of poverty, lacks global economic burden estimates. This study aims to determine the global, regional, and country-level cost of leptospirosis due to loss of productivity. Methodology/principal findings The cost of leptospirosis due to loss of productivity (referred to as productivity cost hereafter) was estimated by converting the disability-adjusted life years (DALYs) lost due to leptospirosis to a monetary value using the per capita gross domestic product (GDP). The country-specific DALYs lost were obtained from the global burden of leptospirosis study published previously. Non-health GDP per capita (GDP- per capita health expenditure) was used for the cost conversion of DALYs. Country-specific GDP and health expenditure data were obtained from the World Bank data repositories. Estimates were done using both nominal and international dollars. The estimated global productivity cost of leptospirosis in 2019 was Int$ 29.3 billion, with low and high estimates ranging from Int$ 11.6 billion to 52.3 billion. China (Int$ 4.8 billion), India (Int$ 4.6 billion), Indonesia (Int$ 2.8 billion), Sri Lanka (Int$ 2.1 billion), and the United States (Int$ 1.3 billion) had the highest productivity cost due to leptospirosis. Eight out of 10 countries with the highest burden were in the Asia-Pacific region. In addition, lower-middle-income countries had an annual productivity cost of Int$ 13.8 billion, indicating that the disease is poverty-related. Conclusion Although significant, the cost estimate due to loss of productivity is merely a fraction of the overall economic burden of this disease, which also includes other direct, indirect, and intangible costs. The existing partial estimates of the different components of economic cost suggest a profound economic burden that demands the inclusion of leptospirosis in the global health agenda for comprehensive disease control and prevention efforts, including vaccine development.